Motivation factors of successful academic research commercialization among Malaysian technical universities - Saida Farhanah, Sarkam (2015)
The Malaysian government has been striving to provide an environment conducive to research commercialisation in the country. Despite the efforts, the targeted research commercialisation rate has yet to be achieved. As such, it is important to understand the motivation of the academic researchers who had successfully commercialised their research. Literature classifies motivation factors as extrinsic, intrinsic, and prosocial, which might exist independently or in a combination (mixed-motivation). Within the academic research commercialisation context, a considerable number of existing studies have discussed the role of extrinsic motivation factors, while the issues of intrinsic and prosocial factors have not been much studied. Thus, this study aimed to further understand the role of each motivation factor as well as the role of mixed-motivation factors among academic researchers who had successfully commercialised their research results. In achieving the study‟s objective, this study utilised the Self-Concordance Theory as the study‟s framework and applied a qualitative case study approach. The informants in the study were the academic researchers from four Malaysian technical universities. The research project was selected as the unit of analysis. The study revealed that academic researchers were highly motivated by the combination of all three motivation factors (mixed-motivation factors) in supporting their commercialisation activities. The recurring themes for all the successful research projects were passion and the personal traits of the academic researchers. The results of this study enrich the Self-Concordance Theory through highlighting the role of the mixed-motivation factors in explaining that the goals of academic researchers‟ commercialisation activities were closely linked to their personal goals